School-based harm reduction with adolescents: a pilot study - Nina Rose Fischer (BMC, 2022)
Abstract A pilot study of Safety First: Real Drug Education for Teens showed significant results pre to post curriculum with high school freshmen. Negative outcomes of drug education are linked to a failure to engage students because of developmentally inappropriate materials that include activities that have no relevance to real experiences of young people. The few harm reduction studies showed increased student drug related knowledge. Students were less likely to consume substances, and less likely to consume to harmful levels. More studies are necessary to evidence harm reduction efficacy in the classroom. The goal of this study was to measure harm reduction knowledge and behaviors, including drug policy advocacy, before and after Safety First. Data were analyzed using McNemar's test, ANOVA, linear regression, t-tests and thematic coding. Survey results, corroborated by the qualitative findings, showed a significant increase (p < .05) in high school freshmen harm reduction knowledge and behaviors in relationship to substance use pre to post Safety First. This increase related to a decrease in overall substance use. Harm reduction is often perceived as a controversial approach to substance use. These findings have implications for further study of what could be a promising harm reduction-based substance use intervention with teens.